Language Learning Strategies and Extraversion/Introversion in the EFL Context - Radić Bojanić, Biljana B. (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Due to the fact that extraverted and introverted personalities behave and react rather differently, especially in the context of foreign language learning, teachers and learners often believe that these two personality types have different learning habits and require different learning environments. This is often reflected in different choices of language learning strategies that these two personality types make, which has already been proven in several research studies. However, these studies did not investigate the selection of language learning strategies in connection to extraversion/introversion among high school students, so this paper aims to determine any possible links for this age group. In order to do that the research relies on the EPQR-S to determine the students’ personality type and Strategy Inventory for Language Learning to determine the participants’ strategy preference. The participants who took part in this research were sixty first- and second-grade students aged 15 to 17 from a medical high school in Novi Sad. The results from this research were analyzed quantitatively and, based on the results, it can be concluded that there are differences in strategy selection. Extraverts use compensation strategies most frequently, while affective strategies are reported to be the least frequently used. Introverts, on the other hand, report the highest use for metacognitive strategies and the lowest for affective strategies, similar to extraverts.